Why the Jenner/Pasteur paradigm is insufficient for controlling vector-borne diseases and the role of microbiota-mediated interactions - Ana Laura Cano-Argüelles; Lianet Abuin-Denis; Dasiel Obregon; Lourdes Mateos-Hernandez; Apolline Maître; Elianne Piloto-Sardiñas; Alejandra Wu-Chuang; Pierre Tonnerre; Alejandro Cabezas-Cruz (Current Research in Parasitology and Vector-Borne Diseases, 2025)
Vaccination campaigns have profoundly influenced the dynamics of infectious diseases, acting as one of the largest ecological experiments in history. By vaccinating billions across decades, we have imposed powerful selective pressures on pathogens, illuminating their ability to adapt, evade, or persist. Rooted in the Jenner/Pasteur paradigm – where exposure to an antigen induces protective immunity – vaccines have revealed how pathogens differ in their ecological susceptibility to immunity. Using this framework, pathogens can be categorized based on their strategies to endure, from those limited by direct immunity to those relying on antigenic variation, chronic infection, or reservoirs. Vector-borne pathogens (VBPs) present a set of challenges to vaccination efforts due to their complex life cycles, stage-specific antigen expression, and reliance on arthropod vectors for transmission. These pathogens not only evade host immunity but also adapt to selective pressures within the vector’s microbiome and immune system. Such complexity often places VBPs beyond the scope of traditional vaccine paradigms, requiring alternative strategies such as transmission-blocking and vector-targeted vaccines. This review explores these insights, examining the interplay between vaccination, pathogen ecology, and evolution – with special emphasis on VBPs – to guide future strategies in vector-borne disease (VBD) control.